Proceedings of the 10th Annual Conference on Genetic and Evolutionary Computation 2008
DOI: 10.1145/1389095.1389277
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous analyses of fitness-proportional selection for optimizing linear functions

Abstract: Rigorous runtime analyses of evolutionary algorithms (EAs) mainly investigate algorithms that use elitist selection methods. Two algorithms commonly studied are Randomized Local Search (RLS) and the (1+1) EA and it is well known that both optimize any linear pseudo-Boolean function on n bits within an expected number of O(n log n) fitness evaluations.In this paper, we analyze variants of these algorithms that use fitness proportional selection.A well-known method in analyzing the local changes in the solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 11 publications
3
56
0
Order By: Relevance
“…It is well-known that fitness proportionate selection without scaling (ν = 1) is inefficient, i. e., it requires exponential optimisation time on simple functions (see [14,24,30]). However, these previous studies often concern the standard mutation rate 1/n, thus it may be possible to optimise OneMax and LeadingOnes in expected polynomial time without scaling but with a different mutation rate.…”
Section: Polynomial Runtime With Standard Fitness Proportionate Selecmentioning
confidence: 99%
“…It is well-known that fitness proportionate selection without scaling (ν = 1) is inefficient, i. e., it requires exponential optimisation time on simple functions (see [14,24,30]). However, these previous studies often concern the standard mutation rate 1/n, thus it may be possible to optimise OneMax and LeadingOnes in expected polynomial time without scaling but with a different mutation rate.…”
Section: Polynomial Runtime With Standard Fitness Proportionate Selecmentioning
confidence: 99%
“…Happ et al (2008) performed the first runtime analysis of fitness proportional selection (f.p.s.) by considering only one individual and bitwise mutation.…”
Section: Algorithm and Proof Strategymentioning
confidence: 99%
“…Happ et al considered variants of the RLS and the (1+1) EA where the plus-selection mechanism is replaced with fitness proportionate selection [5]. They found that changing the algorithms this way makes them highly inefficient on linear functions.…”
Section: Fitness Proportionate Selectionmentioning
confidence: 99%